2015
DOI: 10.11594/jtls.05.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Lipid Peroxidation Activities of Three Selected Fruits Juices Against Cadmium Induced Liver Damage In Vitro

Abstract: Cadmium (Cd) is one of the most toxic heavy metal. Numerous tissues both in vitro and in vivo suggest that Cd induced lipid peroxidation. The presence of antioxidant can inhibit this process. This present study was designed to determine the effects of mango, papaya, and banana juices on malondialdehyde levels (MDA) during Cd exposure in vitro. The result of this study showed that there were a significant difference MDA level between three selected fruits juices. The result of this study also showed the signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Suhartono et al [7] result study showed that subacute and subchronic Cd exposure could increase the level of malondialdehyde (MDA) and advanced oxidation protein products (AOPPs) in kidney homogenates. Furthermore, our several results study showed that Cd exposure could induced oxidative stress, lipid peroxidation, and depletes the enzymatic antioxidant activity in brain, liver, and kidney of rats [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Suhartono et al [7] result study showed that subacute and subchronic Cd exposure could increase the level of malondialdehyde (MDA) and advanced oxidation protein products (AOPPs) in kidney homogenates. Furthermore, our several results study showed that Cd exposure could induced oxidative stress, lipid peroxidation, and depletes the enzymatic antioxidant activity in brain, liver, and kidney of rats [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…(10) AOPPs is known as a cross-linking protein products which are formed by a modification of amino acid caused by oxidation by a ROS. (22)(23)…”
Section: Discussionmentioning
confidence: 99%
“…Sampling Procedure 30 cases of children (16 males and 14 females) aged upto 16 years, having clinical features of DHF as per World Health Organization (WHO), 1997 guidelines for control and prevention of DHF with positive serology were included in this study. 12 Dengue infection was confirmed by IgM/IgG and NS-1 detection. Another 30 age-and gender-matched children attending the Outpatient Department of General Paediatrics for routine check-up were included to serve as controls following simple random sampling method, of which 18 were males and 12 were females.…”
Section: Study Periodmentioning
confidence: 92%